Coffee as a Naturally Beneficial and Sustainable Ingredient in Personal Care Products: A Systematic Scoping Review of the Evidence - Carvalho Neto, Dão Pedro de; Gonot-Schoupinsky, Xavier P.; Gonot-Schoupinsky, Freda N. (Frontiers in Sustainability, 2021)
This systematic scoping review presents evidence from 52 primary research articles for the beneficial, and sustainable, use of coffee in personal care products. The identification and evaluation of natural ingredients that harbour bioactive compounds capable of supporting healthy personal care and protecting and improving the appearance and condition of skin and hair is topical. Demand for natural and sustainable ingredients in beauty and personal care products is driving growth in a market valued at over 500 billion. Coffee, as one of the world’s favourite beverages, is widely studied for its internal benefits. External benefits, however, are less known. Here the potential of coffee and its by-products as ingredients in cosmetic and personal care formulations is explored. Diverse applications of a range of bioactive compounds from the coffee bean, leaves, and by-products, are revealed. Research is evaluated in light of economic and environmental issues facing the coffee industry. Many of the 25 million smallholder coffee farmers live in poverty and new markets may assist their economic health. Coffee by-products are another industry-wide problem, accounting for 8 million tonnes of residual waste per year. Yet these by-products can be a rich source of compounds. Our discussion highlights phenolic compounds, triacyclglycerols, and caffeine for cosmetic product use. The use of coffee in personal care products can benefit consumers and industry players by providing natural, non-toxic ingredients and economic alternatives and environmental solutions to support sustainability within the coffee production chain. Database searches identified 772 articles. Of those included (k = 52), a minority (k = 10; N = 309) related to clinical trials and participant studies. Applications were classified, using the PERSOnal Care products and ingredients classification (PERSOC). Sustainability potential was evaluated with the Coffea Products Sustainability (COPS) model. Overall objectives of the systematic scoping review were to: 1) scope the literature to highlight evidence for the use of coffee constituents in externally applied personal care products, and 2) critically evaluate findings in view of sustainability concerns.